Flexible Tunable Silicon on Insulator Multimode Interference Coupler Using Multi-heater Design - U. Mankong (2020)
© 2019 IEEE. Tunability of silicon multi-mode interference coupler can be achieved by thermo-optic effect. However in previous work, flexibility is limited, since negative change in refractive index cannot be obtained by heater, requiring large power to give required coupling ratio. In this paper we show that by adopting appropriate multi-heater design, we can tune the coupling ratio either increasingly or decreasingly with lower effective refractive index change. The results are shown theoretically using transfer matrix and by finite difference time domain simulation.